2020
DOI: 10.7759/cureus.7162
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal and Extraperitoneal Colonic Perforation Following Diagnostic and Therapeutic Colonoscopy with Crohn’s-related Stricture Dilation

Abstract: Colonic perforation is an uncommon but known and feared complication of colonoscopy, which carries a high mortality rate. We present an uncommon case of extensive intra-and extraperitoneal air following colonic perforation in a patient undergoing inpatient colonoscopy for evaluation of unintentional weight loss and constipation. During colonoscopy, a splenic flexure stricture was identified and dilated. Postprocedural hemodynamic instability prompted further imaging which revealed pneumoperitoneum, bilateral p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…ICP management is tailored to each patient's unique situation and may be conservative, endoscopic, or surgical, with the potential for various surgical techniques [ 16 ]. Weng et al reported a case in which a CD patient had perforation following an endoscopy and was treated surgically with bowel resection at the site of perforation due to the instability exhibited in the patient's status and the extensive complications following ICP [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…ICP management is tailored to each patient's unique situation and may be conservative, endoscopic, or surgical, with the potential for various surgical techniques [ 16 ]. Weng et al reported a case in which a CD patient had perforation following an endoscopy and was treated surgically with bowel resection at the site of perforation due to the instability exhibited in the patient's status and the extensive complications following ICP [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] Few cases reported the presence of SE after colonic perforation complicating colonoscopy. [ 2 3 ] Colonic perforation is a rare complication of colonoscopy with an incidence ranging from 0.04% to 0.7% . 2 It can lead to SE only if the perforation involves the extraperitoneal colon.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] In rare occasions, SE may occur after extraperitoneal colonic perforation following colonoscopy. [ 2 3 ] However, this rare presentation of colonic perforation, particularly without suggestive medical history, may delayed the diagnosis of this life-threatening condition. Informed consent from the patient's family was obtained before writing this case report.…”
Section: Introductionmentioning
confidence: 99%